Photoinduced Cross-Coupling of Amines with 1,2-Diiodobenzene and Its Application in the Synthesis of Carbazoles - Zhao, Xinxin; Chen, Ming; Huang, Binbin; Yang, Chao; Gao, Yuan; Xia, Wujiong (Synthesis, 2018)
A facile and efficient process for the preparation of various tertiary aminobenzenes and carbazole derivatives via photoinduced cross-coupling of amines with 1,2-diiodobenzene is reported. Mechanistic investigations indicate that the transformation proceeds via nucleophilic addition of an amine to the benzyne intermediate accompanied with a proton transfer process, followed by an oxidative cyclization of the generated diphenylamine to furnish the corresponding carbazole products.
Keywords: aminobenzenes; cross-coupling; carbazoles; oxidative cyclization